SWOT Analysis of e-HRM Implementation at PT Kazee Digital Indonesia - Latifa Puspita Putri; Ani Wahyu Rachmawati (Advanced Qualitative Research, 2026)
Electronic Human Resource Management (e-HRM) has become a strategic approach to support the digital transformation of human resource practices in organizations. This study analyzes the implementation of Waktoo, an internally developed e-HRM system at PT Kazee Digital Indonesia, through a qualitative case study. Data were collected using semi-structured interviews, observations, and documentation, and analyzed using Miles and Huberman’s interactive model, supported by manual coding and triangulation to ensure credibility. The SWOT analysis revealed several strengths, including face-detection–based attendance integrated with payroll and a user-friendly interface, while weaknesses included technical bugs, limited use of non-core features, and the absence of training modules. Opportunities include AI integration, HRIS market expansion, and the rising demand for digital HR solutions, whereas threats arise from established commercial HRIS providers, diverse user requirements, and system reliability issues. Based on these findings, strategic recommendations are formulated to optimize Waktoo’s development and competitiveness, such as adding HR development features, enhancing system stability, and strengthening customization capabilities. The study contributes theoretically by integrating SWOT with qualitative insights in evaluating e-HRM adoption and practically by providing strategies for improving the relevance and sustainability of in-house HR digitalization initiatives.